Crystallized Pickering Emulsions from Plant Oil as a Local Alternative to Palm Oil - Cyrill Husmann; Tamara Schmid; Chiara Waser; Ivo Kaelin; Lukas Hollenstein; Nadina Müller (Foods)
Palm and palm kernel oils are preferred ingredients in industrial food processing for baked goods and chocolate-based desserts due to their unique properties, such as their distinctive melting behaviors. However, ongoing concerns about the social and environmental sustainability of palm oil production, coupled with consumer demands for palm oil-free products, have prompted the industry to seek alternatives which avoid the use of other tropical or hydrogenated fats. This project investigated replacing palm oils with chemically unhardened Swiss sunflower or rapeseed oils. Target applications were cookies and chocolate fillings. These oils were physically modified through emulsification, stabilized with finely ground oil press cake particles and crystallized waxes. Findings indicated that the emulsification of the oils increased viscosity and that the addition of wax was beneficial for long-term stability; however, the extent of this effect depended on the combination of oil and wax types. Furthermore, wax pre-crystallization and low shear during crystallization significantly improved emulsion stability. Despite these improvements, the resulting emulsions did not achieve sufficient stability and exhibited lower viscosity than palm oil. Future experiments should explore higher wax concentrations (1% or more) and develop analytical methods to better understand the wax composition and its role in oleogel formation.